2018
DOI: 10.3389/fphys.2018.00886
|View full text |Cite
|
Sign up to set email alerts
|

Resting Metabolic Rate and Lung Function in Wild Offshore Common Bottlenose Dolphins, Tursiops truncatus, Near Bermuda

Abstract: Diving mammals have evolved a suite of physiological adaptations to manage respiratory gases during extended breath-hold dives. To test the hypothesis that offshore bottlenose dolphins have evolved physiological adaptations to improve their ability for extended deep dives and as protection for lung barotrauma, we investigated the lung function and respiratory physiology of four wild common bottlenose dolphins (Tursiops truncatus) near the island of Bermuda. We measured blood hematocrit (Hct, %), resting metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“… The parameters for Equations (4) and (5) in Bostrom et al ( 2008 ) were revised using previously published compliance data from the bottlenose dolphin (Fahlman et al, 2018b ). Old values are in parentheses .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… The parameters for Equations (4) and (5) in Bostrom et al ( 2008 ) were revised using previously published compliance data from the bottlenose dolphin (Fahlman et al, 2018b ). Old values are in parentheses .…”
Section: Methodsmentioning
confidence: 99%
“…Coastal bottlenose dolphins inhabit coastal areas and generally perform short (<60 s), shallow (<10 m) dives (Mate et al, 1995 ), while offshore bottlenose dolphins inhabit offshore, deep-water habitats and regularly dive below 200 m (Klatsky et al, 2007 ). Interestingly, neither resting metabolic rate nor lung compliance differed between the two ecotypes (Fahlman et al, 2018a , b ), but blood hematocrit was significantly higher in the offshore ecotype (Klatsky et al, 2007 ; Schwacke et al, 2009 ; Fahlman et al, 2018a ). In addition, the offshore ecotype is generally larger (Klatsky et al, 2007 ), possibly due to larger muscle mass to help increase the available O 2 stores and diving capacity.…”
Section: Introductionmentioning
confidence: 97%
“…The differential pressure transducer was connected to a data acquisition system (Powerlab 8/35, ADInstruments, Colorado Springs, CO, United States), and the data was captured at 400 Hz and displayed on a laptop computer running LabChart (v. 8.1, ADInstruments, Colorado Springs, CO, United States). A low resistance diffuser was added to homogenize the flow (Fahlman et al, 2018b), which helped resolve the difference in calibration factors for inspired (V insp ) and expired (V exp ) flow (Fahlman et al, 2015). To assess the flow range over which the flow was linear, we used an industrial fan (Atmosphere Vortex 728 CFM S Line S-800 Fan, 8 ) to generate laminar flow up to 120 l • s −1 , as measured by a calibrated industrial flow meter (Merriam Process Technologies, Serial No.…”
Section: Respiratory Flowmentioning
confidence: 99%
“…Respiratory flow (V) is also generally greater in marine mammals as compared with terrestrial species, especially in cetaceans, that have been shown to be able to generate expiratory flows (V exp ) that are at least one order of magnitude greater than in humans (Olsen et al, 1969a;Kooyman et al, 1971Kooyman et al, , 1975Kooyman and Cornell, 1981;Piscitelli et al, 2013;Fahlman et al, 2015Fahlman et al, , 2017Fahlman et al, , 2019b). There appears to be great variability in the mechanical properties of the respiratory system, but in general marine mammals appear to have more compliant lung parenchyma as compared with terrestrial species, and a rib cage that allows the alveoli to compress and collapse without apparent trauma (Olsen et al, 1969b;Leith, 1976Leith, , 1989Fahlman et al, 2011Fahlman et al, , 2017Fahlman et al, , 2018bDenk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Z9A887-2, Merriam Process Technologies, Cleveland, OH, USA). A low-resistance diffuser was added to homogenize the flow (Fahlman et al, 2018c), which helped resolve the difference in calibration factors for inspired (Vi nsp ) and expired (Vė xp ) flow . A differential pressure transducer (Spirometer Pod, ML 311, ADInstruments, Colorado Springs, CO, USA) was connected to the pneumotachometer with two firm-walled, flexible tubes (310 cm length×2 mm i.d.).…”
Section: Respiratory Flowmentioning
confidence: 99%